SURVIVING THROUGH ORGANISED CRIME: ACOMPARATIVE STUDY OF ILLICIT NETWORKS INTRANSNISTRIA AND ABKHAZIA (Journal of Media studies, 2024)
This paper explores the connection between the existence ofillicit networks and the survival of the de facto states of the Republic ofTransnistria and the Republic of Abkhazia. The paper argues that organizedcrime plays a dual role in the continuity of state and society in these regions,both supporting and hindering state-building and the attainment of a strong,independent state. The study first provides a brief overview of organized crimeand its impact on state characteristics. It then delves into the characteristics oforganized crime in Transnistria and Abkhazia separately to draw conclusionsabout their similarities and differences. Finally, the research examines the roleof illicit activities in the survival of these de facto states. The findings suggestthat the presence of illicit networks has significant implications for state survivaland development in post-Soviet de facto states.